1972
DOI: 10.1577/1548-8659(1972)101<420:totidr>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the Insecticide Dursban(R)to Fish and Aquatic Invertebrates in Ponds

Abstract: Bluegills (Lepomis macrochirus Rafinesque) and largemouth bass (Micropterus salmoidesLacepede) were exposed to two applications of Dursban©, an organophosphorus insecticide, at the recommended rates for mosquito control of 0.05 or 0.01 lb of active ingredient/A in experimental 0.! acre ponds. Residues of Dursban in water ! day after the applications ranged from 2.39 parts per billion (ppb) in the highest treatment to 0.97 ppb in the low treatment. Cumulative mortality in the untreated ponds during 63 days of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…By contrast several which suggests that the ditches are still in an early other studies showed no direct effects on oligochadevelopmental stage. This also explains the di-etes (Macek et al, 1969;Nelson & Evans, 1973). Although secondary effects, between 14 and 56 days after treatment, are suggested by van Wijngaarden & Leeuwangh (1989) who reported that oligochaetes decreased in numbers or even vanished.…”
Section: Control Clay Ditchesmentioning
confidence: 82%
“…By contrast several which suggests that the ditches are still in an early other studies showed no direct effects on oligochadevelopmental stage. This also explains the di-etes (Macek et al, 1969;Nelson & Evans, 1973). Although secondary effects, between 14 and 56 days after treatment, are suggested by van Wijngaarden & Leeuwangh (1989) who reported that oligochaetes decreased in numbers or even vanished.…”
Section: Control Clay Ditchesmentioning
confidence: 82%
“…Prolonged AChE inhibition has been found in fish exposed to several organophosphorus insecticides. Macek et al (1972) found that after treatment of ponds with chlorpyrifos at 0.056 kg/ha, brain AChE activity of bluegills and largemouth bass was inhibited by 80%, and did not return to the levels of control fish until 28 d after pulse addition of the pesticide. Enzyme activity in brains of spot remained significantly below pre‐spray levels for more than 40 d after spraying of malathion (Coppage et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of AChE activity is directly related to the concentration of pesticides and the length of exposure (Coppage, 1972;Macek et al, 1972). Koundinya and Ramamurthy (1979) also reported a greater inhibition in AChE activity, with higher elevation in ACh content in the brain than in the muscle of T. mossambica exposed to sumithion.…”
Section: Resultsmentioning
confidence: 99%